PENGARUH PELATIHAN DAN KOMPETENSI TERHADAP KINERJA KARYAWAN MELALUI MOTIVASI PADA PT. CIPTA KRIDA BAHARI JAKARTA DAN SUMATERA AREA - Freddrick Tiagita Putra (Jurnal Manajemen Bisnis Krisnadwipayana, 2016)
The purpose of this study was to test and obtain empirical evidence about the direct and indirect effects of training and competence together to employees performance in PT. Cipta Krida Bahari. This study uses an explanatory approach Analysis and Descriptive Analysis, which aims to determine the effect of independent and dependent variables. Furthermore, the present invention will be described, by observation and research and describe the nature or the events ongoing at the time of the study and examine the causes of the symptoms. In this study examines the influence of variables of training, competence and motivation, simultaneously or partially on employee performance. The benefits of this research is that companies in improving the performance of employees through training programs, attention to improving the competence of employees, increase employee motivation, and in turn can help in improving the work (performance) of each individual employee. The results showed simultaneously and partially variable training and competency positive effect on employee motivation and improve employee performance.